Literasi Numerasi Di Berbagai Konteks Pendidikan Dan Sosial: Tinjauan Sistematis Mengenai Faktor Prediktif, Kesenjangan, Dan Efektivitas Intervensi - Nunuk Haryanti; Afadil; Supriyatman; Citra Dewi; Ni Putu Murniasih; Sarintan Nurcahyati Kaharu (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to synthesize global empirical findings on literacy numeracy (LN) through a Systematic Literature Review (SLR) approach. The review focuses on three key aspects: predictive factors of numeracy development, social disparities (including gender and socioeconomic status), and the effectiveness of pedagogical interventions. Data were collected from 15 empirical studies published between 2024 and 2025 and analyzed using thematic synthesis. The findings reveal that numeracy development is influenced by strong cognitive foundations, particularly early numeracy and quantitative language, which act as significant predictors of later mathematical achievement. Neurocognitive evidence also highlights the role of specific brain regions, while family support contributes indirectly through learning environments. Furthermore, significant social disparities persist, where gender and socioeconomic status interact in complex ways to shape numeracy outcomes, with women and low-SES groups consistently showing lower performance. In terms of interventions, domain-specific and differentiated pedagogical approaches, including teacher professional development and contextualized learning, demonstrate effectiveness in improving numeracy skills. However, challenges remain in implementation, particularly in curriculum alignment, assessment bias, and contextual barriers. This study contributes to a comprehensive understanding of literacy numeracy as a multidimensional and context-dependent competence, emphasizing the need for integrated, equitable, and evidence-based educational strategies.